Germans' Willingness to Pay for Gas and Heating - Teodora Boneva; Armin Falk; Mark Fallak; Lasse Stötzer (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
According to a representative briq survey, two-thirds of the German population would be willing to pay hig-her prices for gas and heating if this were to increase pressure on the Russian government. Four out of five Germans would lower their room temperature to save energy. And more than half of higher-income house-holds would be willing to spend some of their income to help poorer households cope with higher energy prices.
Keywords: 330